Dachristic Seizures with Left Mesial Temporal Sclerosis and During Wada Test - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
Dachristic seizures are characterized by ictal crying during complex partial seizures expressed as an unconscious behavior without sadness.